Surgical Treatment and Outcome of Acquired Midline Palate Defects in Cats - Castejón-González, Ana C.; Stefanovski, Darko; Reiter, Alexander M. (Frontiers in Veterinary Science, 2022)
Acquired midline palate defects (PDE) affect the hard and/or soft palate and result from trauma, commonly falling from a height or being hit by a motor vehicle. Additional life-threating injuries and costs associated with treatment may delay surgical treatment. This retrospective study describes signalment, cause and extent of the PDE, and treatment in 25 cats. In addition, outcome of the surgical repair is described in 19 (76%) cats. All defects were repaired within five days of the injury. Twenty (80%) cats were four years of age or younger. The most common rostral extent of the PDE was to the level of the third premolar tooth (n=8; 32%), incisor teeth (n=7; 28%), and fourth premolar tooth (n=5; 20%). Soft palate laceration was present in all cases. Surgical therapy was successful in all cases with follow-up. The most common techniques used for closure of the hard palate defect were bilateral pedicle flaps with lateral releasing incisions (n=8; 32%), direct apposition of the oral mucosa (n=7; 28%), bilateral pedicle flaps with lateral releasing incisions and interquadrant splinting (n=5; 20%), and unilateral pedicle flap with one lateral releasing incision (n=4; 16%). A tension-free closure by direct apposition of the edges was possible for the soft palate laceration. No oronasal fistulae were identified at follow-up. The only complication was malocclusion. Interquadrant splinting was most often used for PDE extending to the rostral portion of the hard palate (p<0.05). Cats that suffered postoperative malocclusion were significantly more likely to have sustained temporomandibular joint injury, underwent CT scan, or had a feeding tube placed before discharge. Results of this retrospective study indicate that early treatment (within 5 days) of acquired longitudinal defects in the midline of the hard and soft palate is highly successful